Analisis Faktor-Faktor Yang Mempengaruhi Penyaluran Kredit Pada BPR Di Kota Boyolali - Arini Novandalina; Fandil Fandil (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
Credit distribution is the provision of money or equivalent debt, based on a loan agreement between a bank and another party that requires the borrower to repay the debt after a certain period of time with interest. The purpose of this study is to determine the effect of Non-Performing Loans, Capital Adequacy Ratio, and Loan to Deposit Ratio on credit distribution at the People's Economic Bank in Boyolali Regency. The population in this study was 6 Rural Credit Banks in Boyolali Regency. The results of the study indicate that Non-Performing Loans, Capital Adequacy Ratio, and Loan to Deposit Ratio have a significant effect on credit distribution